Perbedaan Retensi Memori pada Mahasiswa Hukum dan Non-Hukum Berdasarkan Levels of Processing - Varadina Dwi Murti; Najwa Nurfadhila Ferika Putri; Fidya Atillah Budiman; Qatrunada Ismed Raudhah; Angela Hafizhah Desky (Jurnal Riset Multidisiplin Edukasi, 2026)
Long-term memory plays an important role in the learning process because it is related to an individual’s ability to store and retrieve information over an extended period. One factor that influences memory retention is the depth of information processing, as explained by the levels of processing theory. This study aimed to compare memory retention between law and non-law students based on levels of processing. The study employed a quantitative approach using a two-group between-subjects quasi-experimental design. Participants consisted of law and non-law undergraduate students selected through purposive sampling. Data were collected through information-processing tasks under deep processing and shallow processing conditions, followed by a free recall test to assess memory performance. The data were analyzed using the Independent Samples t-Test. The results showed that law students obtained higher mean scores than non-law students in both processing conditions. However, the differences were not statistically significant in either the deep processing condition (p = .405) or the shallow processing condition (p = .398). Nevertheless, the effect sizes were in the moderate range, indicating a tendency toward differences in memory retention between the two groups. These findings suggest that academic experiences may contribute to how individuals process and retain information, although further studies with larger sample sizes are needed to obtain more robust results.